Single unit activity in the subiculum of freely-moving rats : spatial and non-spatial correlates - Anderson, Michael Ian (Trinity College (Dublin, Ireland). School of Psychology, 2001)
Compared with the research effort directed at the hippocampus the subiculum has received little experimental attention despite being one synapse downstream of area CAI and in a position to influence many cortical areas with the results of hippocampal activity. Recently, however, the subiculum has been the focus of a greater interest. The subiculum is a pivotal structure positioned between the hippocampus proper and entorhinal and other cortices, as well as a range of subcortical structures. The subiculum has a range of electrophysiological and functional properties which are quite distinct from its input areas; given the widespread set of cortical and subcortical areas with which it interacts, it is able to influence activity in quite disparate brain regions. However, its functional properties are not wellunderstood; it plays an important but ill-defined role both in spatial navigation and in mnemonic processing.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin